Uvite, CaMg3(Al5Mg)(Si6O18)(BO3)3(OH)3(OH), a new, but long-anticipated mineral species of the tourmaline supergroup from San Piero in Campo, Elba Island, Italy. (31st October 2022) - Bosi, Ferdinando; Biagioni, Cristian; Pezzotta, Federico; Skogby, Henrik; Hålenius, Ulf; Cempírek, Jan; Hawthorne, Frank C.; Lussier, Aaron J.; Abdu, Yassir A.; Day, Maxwell C.; Fayek, Mostafa; Clark, Christine M.; et al.
Abstract: Uvite, CaMg3 (Al5 Mg)(Si6 O18 )(BO3 )3 (OH)3 (OH), is a new mineral of the tourmaline supergroup. It occurs in the Facciatoia quarry, San Piero in Campo, Elba Island, Italy (42°45′04.55″N, 10°12′50.89″E) at the centre of a narrow (2–3 cm wide) vein composed of aggregates of dark brown to black tourmaline, penetrating (magnesite + dolomite)-rich hydrothermally altered metaserpentinite. Crystals are euhedral and up to 1 cm in size, brown with a vitreous lustre, conchoidal fracture and grey streak. Uvite has a Mohs hardness of 7½, a calculated density of 3.115 g/cm 3 and is uniaxial (–). Uvite has trigonal symmetry, space group R 3 m, a = 15.9519(10) Å, c = 7.2222(5) Å, V = 1597.3(1) Å 3 and Z = 3. The crystal structure was refined to R 1 = 1.77% using 1666 unique reflections collected with Mo K α X-rays. Crystal-chemical analysis resulted in the empirical crystal-chemical formula ^X (Ca_0.61Na_0.35 _0.04)_Σ 1.00^Y ( Mg_1.50Fe^2 + _0.47 Al_0.71Fe^3 + _0.14 Ti_0.18 )_Σ 3.00 ^Z ( Al_4.54Fe^3 + _0.18 V^3 + _0.02 Mg_1.27 )_Σ 6.00^T[ ( Si_5.90Al_0.10 )_Σ 6.00O_18 ] ( BO_3 )_3^ ^O(3)( OH )_3^O( 1 ) [( OH )_0.55F_0.05O_0.40]_Σ 1.00 which recast in its ordered form for classification purposes is: & ^X (Ca_0.61Na_0.35_0.04)_Σ 1.00^Y ( Mg_2.35Fe^2 + _0.47 Ti_0.18 )_Σ 3.00 & ^Z ( Al_5.25Fe^3 + _0.32 V^3 + _0.02 Mg_0.42 )_Σ 6.00^T [ ( Si_5.90Al_0.10 )_Σ 6.00O_18 ]( BO_3 )_3^V ( OH )_3^W [( OH )_0.55F_0.05O_0.40]_Σ 1.00 Uvite is a hydroxy-species belonging to the calcic-group of the tourmaline supergroup. The closest end-member compositions of valid tourmaline species are fluor-uvite and feruvite, to which uvite is related by the substitutions W (OH) – ↔ W F – and Y Mg 2+ ↔ Y Fe 2+, respectively. The occurrence of a solid-solution between uvite and magnesio-lucchesiite, according to the substitution Z Mg 2+ + W (OH) – ↔ Z Al 3+ + W O 2–, is supported by experimental data. The new mineral was approved by the IMA–CNMNC (IMA 2019-113). Uvite from Facciatoia formed by the reaction between B-rich fluids, released during the crystallisation process of LCT pegmatites, and the surrounding metaserpentinites, altered by contact metamorphism in the aureole of the Miocene Mt. Capanne monzogranitic pluton.